Omeprazole and adenocarcinoma in the stomach of rats submitted to duodenogastric reflux. Is there a protective effect? - Monteiro, Rosângela Lucinda Rocha; Kobayasi, Maria Aparecida Marchesan Rodrigues [UNESP]; de Araujo, Marina Rachel; Monteiro, Dafny Rocha; Andreollo, Nelson Adami (FapUNIFESP (SciELO), 2020)
Purpose: To investigate the role of omeprazole and nitrites on the gastric mucosa of rats submitted to specific techniques to induce duodenogastric reflux. Methods: One hundred and twenty Wistar rats were divided into three groups: Group I (n=40) – gastrotomy; Group II (n=40) – duodenogastric reflux after gastrojejunoanastomosis latero-lateral (DGR); Group III (n=40) – retrograde duodenogastric reflux through the pylorus (DGR-P). The groups were divided into 4 subgroups of 10 animals, respectively treated for 16 weeks with water, omeprazole 1.6 mg / rat / day, nitrite 600 mg / kg / day and omeprazole plus nitrite simultaneously. Results: The proliferative lesions found were: squamous hyperplasia – 69.1%, adenomatous hyperplasia in the anastomosis – 29.1% and prepyloric adenomatous hyperplasia – 42.5%. Adenocarcinomas were registered in 7 animals (5.8%): one in Group I (omeprazole plus nitrite), two in Group II (omeprazole and nitrite plus omeprazole) and four in Group III (water, nitrite, omeprazole and omeprazole plus nitrite). Conclusions: The occurrence of squamous hyperplasia, adenomatous hyperplasia and adenocarcinoma increased after gastrojejunal anastomoses, which cause duodenogastric reflux. The association of omeprazole did not protect the development of proliferative lesions and cancer induced by duodenogastric reflux in rats.
Keywords: Carcinogenesis; Duodenogastric Reflux; Nitrites; Omeprazole; Rats